(untitled) - Phạm, Lan Anh (Can Tho, 2009)
The research aims to find out whether indirect feedback helps reduce grammatical errors in students' writing assignments. It also considers students' attitudes toward indirect feedback.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu